Study the frequency of bronchial anthracosis and its influencing factors in patients undergoing bronchoscopy in Ardabil city hospital, 2013-2015 - Hoseininia, Saeid; Kebar, Susan Mohammadi-; Kheir, Keysan Ghadam- (International Journal Of Community Medicine And Public Health, 2020)
Background: Bronchial anthracosis is defined as appearance of multiple dark anthracotic pigmentations on large airway mucosa with or without airway narrowing or obliteration. This study aims to investigate the frequency of bronchial anthracosis and its influencing factors in patients undergoing bronchoscopy. Methods: In this cross-sectional study, data was obtained from reviewing the files of 900 patients who underwent bronchoscopy in Ardabil city Hospital. Those with dark pigmentation on their airways mucosa were considered as having bronchial anthracosis. During bronchoscopy, samples were collected from the airways in the form of bronchoalveolar lavage and then the smear and culture of these samples were examined for acid fast bacilli. Type of fuel used for cooking in the kitchen and for heating in their house, history of smoking, the patient’s geographical location and occupation were recorded by a checklist and then evaluated. Results: Of 900 cases, 42 (4.6%) had bronchial anthracosis, out of which 23 (55%) were male and most were in urban areas. Majority of patients were in the age range of 60 to 70 years. Of 11 farmers with anthracosis, 7(6.63%) patients used fossil fuels for heating. Among the anthracosis patients, 11 (21.2%) subjects had Tuberculosis. There was a significant difference between age, habitant of patients, pulmonary tuberculosis and bronchial anthracosis. Conclusions: There was a significant correlation between age of patients, pulmonary tuberculosis and bronchial anthracosis, therefore, performing necessary tests and follow-ups for pulmonary tuberculosis is necessary in cases that undergo bronchoscopy for any reason and those with bronchial anthracosis.